In-situ experimental and computational approach to investigate the nature of active site in low-temperature CO-PROX over CuOx-CeO2 catalyst - Adak, Shubhadeep; Rabeah, Jabor; Ranjan, Ravi; Khan, Tuhin Suvra; Poddar, Mukesh Kumar; Gupta, Rishi Kumar; Sasaki, Takehiko; Kumar, Sagar; Bordoloi, Ankur; Gopinath, Chinnakonda S.; Bruckner, Angelika; Bal, Rajaram (Applied Catalysis A-General, 2021)
Preferential oxidation (PROX) of carbon monoxide (CO) in presence of excess hydrogen is a necessity to prevent poisoning of the Pt-anode by CO in PEMFCs (Polymer Electrolyte Membrane Fuel Cell). A highly active catalyst, 5 wt% Cu-CeO2 showed 100 % CO conversion at 65 degrees C without any undesirable oxidation of H-2. The catalyst showed no deactivation even after 100 h on stream, making it viable for practical fuel cell application. Operando EPR in the PROX reaction condition revealed highly dispersed mixed valent cations with oxygen vacancies, responsible for the low-temperature PROX activity. At the active site, both Cu and Ce ions were shown to reversibly change their valence states to facilitate the abstraction of bridging lattice oxygen for CO oxidation to CO2. This surface oxygen mediated CO oxidation was found to be much faster than that of H-2 to H2O, which could explain the complete selectivity of oxygen for CO2 formation.
Keywords: CuOx-CeO2; interface; Oxygen vacancy; PROX; Synergistic